Primary postpartum haemorrhage in women with von Willebrand disease or carriership of haemophilia despite specialised care: a retrospective survey. (16th February 2015) - Stoof, S. C. M.; van Steenbergen, H. W.; Zwagemaker, A.; Sanders, Y. V.; Cannegieter, S. C.; Duvekot, J. J.; Leebeek, F. W. G.; Peters, M.; Kruip, M. J. H. A.; Eikenboom, J.
Summary Pregnant women with bleeding disorders require specialised peripartum care to prevent postpartum haemorrhage (PPH). If third trimester coagulation factor levels are <0.50 IU mL−1, prophylactic treatment is indicated and administered according to international guidelines. However, optimal dose and duration are unknown and bleeding may still occur. The aim of this study was to investigate the outcome in women with von Willebrand disease (VWD) or haemophilia carriership treated according to current practice guidelines. From the period 2002–2011, 185 deliveries in 154 VWD women or haemophilia carriers were retrospectively included. Data on blood loss, bleeding disorder characteristics and obstetric risk factors were obtained. The outcome was primary PPH, defined as blood loss ≥500 mL within 24 h postpartum and severe PPH as blood loss ≥1000 mL. Primary PPH was observed in 62 deliveries (34%), 14 (8%) of which resulted in severe PPH. In 26 deliveries prophylactic treatment was administered due to factor levels below the 0.50 IU mL−1 cut‐off in the third trimester, 14 of which (54%) were complicated by PPH. We found an increased PPH risk in deliveries given prophylactic treatment compared with deliveries without (OR 2.7, 95% CI 1.2–6.3). In conclusion, PPH incidence was highest in deliveries with the lowest factor levels in the third trimester. Currently, delivery outcome in women with bleeding disorders is unsatisfactory, given the high PPH incidence despite specialised care. Future studies are required to optimise management of deliveries in this patient population.